Comparative Study of Saline Sono Salpingography (SSG) and Laparoscopy with Chromopertubation in Evaluation of Tubal Patency (Journal of Shaheed Suhrawardy Medical College, 2019)
Background In the field of infertility, tubal factor has a great role. So the assessment of tubal patency belongs to the initial diagnostic tests in the work-up of an infertile woman. During the past few years, sonosalpingography has been suggested as the firstline method to study tubal patency. This comparative study of transvaginal saline SSG to the gold standard method of diagnostic laparoscopy with chromopertubation was performed for the assessment of tubal patency in infertile women.Methods At first thirty-four patients suffering from primary or secondary infertility were evaluated for tubal patency with sonosalpingography using a pediatric Foley urinary catheter using saline solution as a contrast medium. The uterine tubes were evaluated. One patient conceived and two patients denied before the scheduled laparoscopy. Ultimately they were excluded from the study. In the study, finally 31 patients were enrolled and the results of SSG were compared to the findings of laparoscopy and chromotubation performed independently.Results The findings of both methods agreed in 26 out of 31 tubes (concordance, 93.5%). The sensitivity of sonosalpingography in diagnosing tubal patency was 96.2% and the specifcity 80%. The positive predictive value for tubal patency by sonosalpingography was 96.29% and the negative predictive value 80%. Adverse events of sonosalpingography included mild abdominal pain in some patient. No infectious complications were recorded.Conclusions The results confirm that sonosalpingography using saline as a contrast medium is a reliable, simple and well-tolerated method to assess tubal patency in an outpatient setting. In addition, the procedure can be performed without prophylactic antibiotics.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 52-58